Practical Aspects Of Teaching Medical Terminology In A Modern University - Buranova Nilufar Shavkatovna (Genius Journals, 2025)
The article presents an in-depth analysis of practical and methodological aspects of teaching medical terminology in modern higher education. It explores the historical background of the discipline’s development, the cognitive and competence-based approaches, and the latest pedagogical technologies used in medical universities. Special attention is paid to the integration of Latin terminology with medical disciplines, the use of digital resources, and the development of terminological thinking and professional speech among students
Keywords: medical terminology; higher education; Latin language